CITA/NLRC5: A critical transcriptional regulator of MHC class I gene expression. (18th April 2016) - Downs, Isaac; Vijayan, Saptha; Sidiq, Tabasum; Kobayashi, Koichi S.
Abstract: Major histocompatibility complex (MHC) class I and class II molecules play essential roles in the development and activation of the human adaptive immune system. An NLR protein, CIITA (MHC class II transactivator) has been recognized as a master regulator of MHC class II gene expression, albeit knowledge about the regulatory mechanism of MHC class I gene expression had been limited. Recently identified MHC class I transactivator (CITA), or NLRC5, also belongs to the NLR protein family and constitutes a critical regulator for the transcriptional activation of MHC class I genes. In addition to MHC class I genes, CITA/NLRC5 induces the expression of β2 ‐microglobulin, TAP1 and LMP2, essential components of the MHC class I antigen presentation pathway. Therefore, CITA/NLRC5 and CIITA are transcriptional regulators that orchestrate the concerted expression of critical components in the MHC class I and class II pathways, respectively. © 2016 BioFactors, 42(4):349–357, 2016